A Family of Planar Luminogens with Active Photoluminescence in both Dispersion and Aggregation States. Issue 8 (12th May 2022) - Hu, Renjian; Lin, Shiyun; Huang, Hongye; Xie, Wensheng; Wang, Mengshi; Li, Ruoxin; Tian, Mei; Shuai, Zhigang; Wei, Yen
Abstract: Molecular skeletons with active photoluminescence emission in both dispersed and aggregated states are important for diverse applications. As planarization of molecular configuration in the excited state has been shown to be a critical precondition for efficient emission, developing luminogens with pristine planar geometry seem to be the most straightforward approach. However, conventional planar ACQ‐type (aggregation‐caused quenching) luminogens (e. g. perylene) or novel planar AIE‐type (aggregation‐induced emission) luminogens exhibit week emission in the aggregated or dispersed states, respectively. Herein, we describe the synthesis of a family of pristine planar luminogens which demonstrate photoluminescence in both the dispersion and aggregation states. The avoidance of a concentration quenching effect in the solid state could be attributed to weakened π–π interactions within the herringbone featured crystal structures based on experimental and theoretical evidence. We further investigated the potential applications of these luminogens in cell imaging. Abstract : We are family : A series of planar luminogens which demonstrate photoluminescence in both dispersion and aggregation states are reported. Their counter‐intuitive emissive behavior has been investigated through X‐ray crystallography and theoretical calculations.